2003
DOI: 10.1029/2003gl017575
|View full text |Cite
|
Sign up to set email alerts
|

Permeability reduction of a natural fracture under net dissolution by hydrothermal fluids

Abstract: Flow‐through tests are completed on a natural fracture in novaculite at temperatures of 20°C, 80°C, 120°C, and 150°C. Measurements of fluid and dissolved mass fluxes, and concurrent X‐ray CT imaging, are used to constrain the progress of mineral dissolution and its effect on transport properties. Under constant effective stress, fracture permeability decreases monotonically with an increase in temperature. Increases in temperature cause closure of the fracture, although each increment in temperature causes a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 15 publications
3
115
0
1
Order By: Relevance
“…The more limited studies on fractures (MOORE et al, 1994;LIN et al, 1997;DURHAM et al, 2001;POLAK et al, 2003) amplify these observations, indicating an increased sensitivity to HMC (hydro-mechanical-chemical) processes, even at temperatures as low as 100 C, where the mobile phase is silica, and the test duration is of the order of a month (ELIAS and HAJASH, 1992;LIN et al, 1997), where permeability may be reduced by a factor of 10,000 times (LIN et al, 1997). Recent experimental results involving the circulation of hydrothermal fluids (20 C-150 C) through a natural fracture in novaculite YASUHARA et al, 2004) have also shown reductions in permeability of over two orders-of-magnitude within the period of one month, and of spontaneous switching between permeability reduction and permeability increase as only temperatures and flow rates were changed.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The more limited studies on fractures (MOORE et al, 1994;LIN et al, 1997;DURHAM et al, 2001;POLAK et al, 2003) amplify these observations, indicating an increased sensitivity to HMC (hydro-mechanical-chemical) processes, even at temperatures as low as 100 C, where the mobile phase is silica, and the test duration is of the order of a month (ELIAS and HAJASH, 1992;LIN et al, 1997), where permeability may be reduced by a factor of 10,000 times (LIN et al, 1997). Recent experimental results involving the circulation of hydrothermal fluids (20 C-150 C) through a natural fracture in novaculite YASUHARA et al, 2004) have also shown reductions in permeability of over two orders-of-magnitude within the period of one month, and of spontaneous switching between permeability reduction and permeability increase as only temperatures and flow rates were changed.…”
Section: Introductionmentioning
confidence: 92%
“…These characterizations explain the enigmatic observation that fractures gape with net dissolution (DURHAM et al, 2001;POLAK et al, 2003). Specifically in this work, process-based models are applied to quantify rates of fracture closure observed in prior experimental data where the role of free-face dissolution is shown important (e.g., the experimental results of POLAK et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains a challenge to perform process-oriented experiments that are carried out at a X-ray CT scanner due to the constrains of the sizes of the working space and by the ability to run fluid flow lines to and from the fluid flow cell, since additionally, there is the need, in many cases, for the attached fluid lines to be able to rotate (180° up until 360°) with the sample as it rotates in the beam (Wildenschild and Sheppard, 2012). Using calculations derived from fluid flow modelling, based on 3D images from techniques like micro-CT (Petchsingto and Karpyn, 2009), predictions on diffusion of contaminants can be estimated (Polak et al, 2003). Based on these calculations, suggestions on possible remediation efforts like clean water injection into the fractures can be tested.…”
Section:  Fluid Flow Analysismentioning
confidence: 99%
“…The dominance of this pressure solution effect is notably due to mechanical loading and the effective pressure applied to the fracture (McGuire et al 2013). The two types of dissolution phenomena may impact differently on the hydraulic behaviour and permeability of the fracture: the channelling effects induced by free face dissolution and giving rise to increase in the fracture's permeability can be offset by the chemical attack on the fracture asperities in contact which, conversely, brings about a decrease in the hydraulic opening and thus the permeability (Polak et al 2003). When the fracture is at the same time submitted to a normal stress, a mechanical closure is superimposed to these closures/apertures due to chemical phenomena.…”
mentioning
confidence: 99%
“…This validation requires, among other things, an understanding of the chemical phenomena occurring within the fracture and the changes in the fracture's morphology. A number of recent studies (Polak et al 2003;Yasuhara et al 2006;McGuire et al 2013;Zhao et al 2014) are devoted to chemical interactions in fractures and, in particular, to the different types of mineral dissolution patterns. Two types of dissolution phenomena are identified: those of the free face dissolution type and those of the pressure solution type.…”
mentioning
confidence: 99%